Photochemical characterization of a novel fungal rhodopsin from Phaeosphaeria nodorum - Fan, Ying; Solomon, P.; Oliver, Richard; Brown, L. (Elsevier BV, 2011)
Eukaryotic microbial rhodopsins are widespread bacteriorhodopsin-like proteins found in many lower eukaryotic groups including fungi. Many fungi contain multiple rhodopsins, some significantly diverged from the original bacteriorhodopsin template. Although few fungal rhodopsins have been studied biophysically, both fast-cycling light-driven proton pumps and slow-cycling photosensors have been found. The purpose of this study was to characterize photochemically a new subgroup of fungal rhodopsins, the so-called auxiliary group. The study used the two known rhodopsin genes from the fungal wheat pathogen, Phaeosphaeria nodorum. One of the genes is a member of the auxiliary group while the other is highly similar to previously characterized proton-pumping Leptosphaeria rhodopsin. Auxiliary rhodopsin genes from a range of species form a distinct group with a unique primary structure and are located in carotenoid biosynthesis gene cluster. Amino acid conservation pattern suggests that auxiliary rhodopsins retain the transmembrane core of bacteriorhodopsins, including all residues important for proton transport, but have unique polar intramembrane residues. Spectroscopic characterization of the two yeast-expressed Phaeosphaeria rhodopsins showed many similarities: absorption spectra, conformation of the retinal chromophore, fast photocycling, and carboxylic acid protonation changes. It is likely that both Phaeosphaeria rhodopsins are proton-pumping, at least in vitro.We suggest that auxiliary rhodopsins have separated from their ancestors fairly recently and have acquired the ability to interact with as yet unidentified transducers, performing a photosensory function without changing their spectral properties and basic photochemistry.